The Ethical and Policy Implications of Epigenetic Research: An Analysis of the TCPS 2 - Gretchev, Andrea; Temples, Heide; Dewey, Deborah; England-Mason, Gillian; Boccuto, Luigi; Haley-Zitlin, Vivian (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Epigenetics is the study of potentially heritable molecular modifications to DNA and chromatin, which can alter the regulation of gene expression. Epigenetic research can potentially inform new risk assessment, diagnosis, and treatment approaches. Purpose: This analysis seeks to identify whether Canada’s Tri-Council Policy Statement: Ethical Conduct for Research Involving Humans 2 (TCPS 2) provides comprehensive protection for the conduct of epigenetic research. These findings could inform policy amendments and future policy development that is inclusive of epigenetics and emerging areas of genomic technology. Additionally, this information benefits individuals or groups conducting epigenetic research. Background: Epigenetic research poses nuanced and distinct ethical challenges that differ from those in other areas of genomic research. This paper applies the Walt and Gilson policy analysis triangle (context, content, process, and actors) to evaluate the adequacy of the TCPS 2 in providing protection for research ethics that extends to epigenetics. Ethical and Policy Analysis: The TCPS 2 offers extensive guidance for genetics research, which is strongly applicable and extends appropriately to epigenetic-specific research. However, subsequent revisions would benefit from modifying the definition of ‘genetics’ to use the more inclusive term ‘genomics’ and explicitly extending it to other genomic research approaches, including epigenetics. Furthermore, broad consent should be transparent about the possibility that data may be used for research involving genomic technologies different from those in the original study. Conclusion: The TCPS 2 provides a strong foundation for ethical epigenetics research. However, minor amendments would provide more comprehensive protection for participants and researchers, ensuring the policy remains relevant and adequate for this rapidly evolving field.